2015
DOI: 10.3748/wjg.v21.i22.7014
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies for colorectal carcinoma with synchronous liver metastases: Which way to go?

Abstract: None of the aforementioned strategies appears inferior. It is necessary to establish individual treatment plans in multidisciplinary team meetings through careful appraisal of all strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 44 publications
1
32
0
4
Order By: Relevance
“…The influence of the timing of hepatectomy on survival remains unclear. A 2015 review of available treatment strategies for synchronous CRLM discussed following four approaches used in clinical practice: primary tumour resection; simultaneous resection; a chemotherapy‐first approach; and upfront hepatectomy. The review concluded that no single method was superior, and advised careful appraisal on a case‐by‐case basis before selecting an approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of the timing of hepatectomy on survival remains unclear. A 2015 review of available treatment strategies for synchronous CRLM discussed following four approaches used in clinical practice: primary tumour resection; simultaneous resection; a chemotherapy‐first approach; and upfront hepatectomy. The review concluded that no single method was superior, and advised careful appraisal on a case‐by‐case basis before selecting an approach.…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 review of available treatment strategies for synchronous CRLM discussed following four approaches used in clinical practice: primary tumour resection; simultaneous resection; a chemotherapy‐first approach; and upfront hepatectomy. The review concluded that no single method was superior, and advised careful appraisal on a case‐by‐case basis before selecting an approach. The observation period of the present study was before publication of the liver‐first surgical approach by Mentha and colleagues, although liver‐first surgery combined with the watch‐and‐wait strategy for rectal cancer may be a future approach for rectal cancer liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The debate over whether or not to perform simultaneous liver resection for CRLM has changed over the past decade; in light of improvements in surgical techniques and postoperative care, simultaneous resection for synchronous CRLM has been performed more often (16,17,18,24), and simultaneous resection has become the treatment of choice in many medical facilities. In fact, the data as a whole strongly suggest imaging studies and verified with increased serum CEA level).…”
Section: Clinical Datamentioning
confidence: 99%
“…Advancements in the management of metastatic intraabdominal malignancies seeking not just to palliate but to push boundaries on achieving significant improvements in overall survival have been contingent upon the identification of subgroups of each metastatic malignancy who may best benefit from targeted, multimodality therapeutic interventions. Examples include the application of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) in colorectal, appendiceal mucinous neoplasms and ovarian metastases to the peritoneum, and the use of metastasectomy in isolated colorectal and neuroendocrine metastases to the liver . With the growing interest in improving survival outcomes in patients with metastatic gastric cancer, it is hence imperative that we examine how the site(s) of metastasis and other clinical features affect the clinical course and overall survival of metastatic gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In pushing the frontiers of managing patients with metastatic disease to achieve further improvements in long‐term survival, we have seen notable results best characterized by colorectal cancer. Colorectal cancer patients with limited metastatic disease isolated to a single site amenable to surgical resection have been shown to benefit from a multimodality approach encompassing systemic chemotherapy, cytoreductive surgery and hyperthermic intraperitoneal chemotherapy …”
Section: Introductionmentioning
confidence: 99%